Meningkatkan Aktivitas Gerak Jasmani Pada Anak Sekolah Dasar Melalui Senam Ria Anak - naufal ardhana; Izzatul Haqiqi; Fikri Farrasyah Putra; Gilang Nuari Panggraita; Nur Annisa Putri (STKIP Muhammadiyah Kuningan Secretariat Jurnal Muhammadiyah Untuk Olahraga Indonesia. Building A106 Street of Murtasiah Soepomo No 28b, 45511 Kuningan - West Java Telephone : 0232-874085 Homepage : E-mail:, 2023)
This article is the result of dedication to elementary school children through children's fun gymnastics in partnership with an elementary school located at SDN 03 Kedungwuni, Gembong Gang Hamlet. Beringin 1 No. 23 Kedungwuni, Kedungwuni District. take part in this dedication program.The program that will be carried out together with partners is Ria Gymnastics for children improve physical fitness.The method of implementing this activity is carried out onmutual agreement, this service activitygiven 1 meeting within 3 hours, this gymnastics service was carried out on Thursday at 07.00 WIB to 10.00 WIB on the sdn page 03 kedungwuni.The results achieved from ink activities namelyElementary school students 03 kdw have good and better physical fitness , have a routine agenda every week to do gymnastic activitiesKeywords: gymnastics, physical fitness